Rethinking national temporal orders: the subaltern presence and enactment of the political. Issue 4 (11th January 2016) - Väyrynen, Tarja
Abstract: How the past is remembered is fundamental to the production and reproduction of postwar sovereign political power. However, Internation Relations' (IR) explicit interest in the practices of remembrance, and particularly in time remains a relatively new one. This article seeks to show how Jacques Rancière's discussion of temporality, subaltern history, and politics – which allows the study of parallel and enmeshing temporal universes – contributes to the IR literature on time. In this view, when speech is acquired by those whose right to speak is not recognised they can produce temporalities that disturb hegemonic representations of time constellations and reorganise the nation's relationship to its past. The article analyses the moment of Kaisu Lehtimäki's telling her war story in public, and understands it to be a material and symbolic event that shatters the hegemonic distribution of the Finnish postwar national history and truth.